Gambaran Dentokraniofasial Arah Vertikal Penderita Gigit Terbuka dengan Anterior Tongue Thrust - Elizabeth Geophine; Erwin Siregar; Krisnawati Krisnawati (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of this study was to investigate the pattern, mean and differences of measurements between men and women on vertical dentocraniofacial cephalometric values of open bite subjects with anterior tongue thrust. There were 27 subjects between ages of 12-28 years, 6 men and 21 women of which thirteen vertical dentocraniofacial variables were obtained from measurements taken from lateral cephalometrics; ANS-Me, N-Me, S-Go, CC-Go, SN-MP, N-ANS, PP-MP, Y-axis, UPDH, LPDH, ANS-UI, LI-MP and overbite. The means of values of ANS-Me, N-Me S-Go and CC-Go were compared with the norms based on Deuteromalay population and SN-MP, PP-MP, Y-axis UPDH, LPDH, ANS-UI, LI-MP with the norms based on Caucasian population. The obstacle of this study was the unavailable norms of vertical dentocraniofacial cephalometric for Deuteromalay population. Generally the pattern of vertical dentocraniofacial of open bite subjects with anterior tongue thrust shows the long face syndrome.